An Efficient Method for Calculating Hysteretic Dry Friction Response of Dynamic Systems Subjected to Combined Harmonic and Random Excitation - Hickey, John (My University, 2024)
Many examples of dynamic analysis require modelling of dry friction. Often this is represented by a so-called Jenkins element or multiple Jenkins elements in parallel, which is sometimes termed a parallel-series Iwan element. This study considers the case where a system that includes these representations of dry friction are loaded dynamically with a combination of deterministic harmonic and random excitation. This paper presents a new efficient method for predicting the response of systems subject to combined deterministic and random excitation. The method is based on equivalent linearisation and involves averaging across both an ensemble of random responses as well as over a harmonic excitation period. The key novelty in the approach is the use of an auxiliary harmonic term to facilitate an analytical representation of the nonlinear force. This overcomes the challenge of analysing a discontinuous hysteretic nonlinearity in the presence of random excitation. Analytical solutions are presented and it is shown that the proposed approach can predict the approximate response at a significantly reduced computational cost.
PUBLISHED
Keywords: Nonlinear dynamics, Friction, Hysteretic Nonlinearity, Equivalent Linearization, Combined Excitation; Smart & Sustainable Planet; FRICTION; Random Vibrations and Stochastic Mechanics; Vibration and Accoustic Engineering